Efficacy of shock wave therapy and ultrasound therapy in non-insertional Achilles tendinopathy: a randomised clinical trial - Stania, Magdalena; Słomka, Kajetan J.; Juras, Grzegorz; Król, Tomasz; Król, Piotr (Frontiers in Neurology, 2024)
Objective Physiotherapists and physicians continue to seek effective conservative treatments for Achilles tendinopathy. This study aimed to subjectively and objectively determine the therapeutic efficacy of radial shock wave therapy (RSWT) and ultrasound therapy in non-insertional Achilles tendinopathy. Materials and methods Thirty-nine patients with non-insertional Achilles tendinopathy were randomly assigned to three experimental groups, i.e., RSWT (group A), ultrasound therapy (group B), and placebo ultrasound (group C) groups. Before the intervention and at weeks 1 and 6 after the treatment, the patients were assessed using the Victorian Institute of Sport Assessment–Achilles (VISA-A) questionnaire and posturographic measurements of step initiation performed on the force platforms under two different conditions (non-perturbed transit and perturbed transit). Results Six weeks after therapy, all groups exhibited significantly increased VISA-A scores against the measurement at week 1 after therapy. The post-therapy percentage changes in VISA-A scores were significantly greater in group A compared to group B. The three-way ANOVA demonstrated that treatment type affected sway range in the frontal plane and mean velocity of the centre of foot pressure displacements in the sagittal and frontal planes during quiet standing before step initiation. The Bonferroni post-hoc test showed that the means of all those variables were significantly smaller for group A than for group B patients. The three-way ANOVA revealed an effect of the platform arrangement on transit time and double-support period. The Bonferroni post-hoc test revealed statistically longer transit time for the perturbed vs. non-perturbed trials; a reverse relationship was observed for the double-support period. Conclusion The VISA-A showed that RSWT was significantly more effective than sonotherapy for alleviation of pain intensity as well as function and activity improvement in patients with non-insertional Achilles tendinopathy. Therefore, RSWT therapy can be used in clinical practice by physiotherapists to alleviate the symptoms of non-insertional Achilles tendinopathy. Objective data registered by force platforms during quiet standing before and after step initiation did not prove useful for monitoring the progress of treatment applied to patients with non-insertional Achilles tendinopathy between consecutive therapy interventions. Clinical trial registration:https://anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12617000860369, identifier (ACTRN12617000860369).